Rapid isolation of pan-neutralizing antibodies against Omicron variants from convalescent individuals infected with SARS-CoV-2 - Yu, Peng; Ran, Jingping; Yang, Ruiqi; Zhu, Hang; Lu, Song; Wu, Yuzhang; Zhao, Tingting; Xiong, Tianchen (Frontiers in Immunology, 2024)
Therapeutic antibodies serve as a crucial weapon in battle against coronavirus infections.Currently, SARS-CoV-2 Omicron subvariants have spread worldwide and posed a major threat to global public health due to their resistance to most antibodies developed during the early stages of the pandemic. Here, by using a rapid antibody discovery platform (Berkeley Lights Beacon), we isolated two monoclonal neutralizing antibodies (2173-A6 and 3462-A4) targeting the receptor-binding domain (RBD) of the spike (S) glycoprotein from individuals recently recovered from Omicron infection. Both 2173-A6 and 3462-A4 exhibit high RBD binding affinity and effectively neutralize pseudoviruses from various Omicron lineages, including BA.4/5, XBB.1.16, XBB.1.5 and EG.5.1 through binding to identical or overlapping epitopes.Taken together, our utilization of the Beacon platform enabled isolation and identification of neutralizing antibodies within less than 10 days. This expedited process will significantly reduce the time required for the development of novel therapeutic antibodies for unknown infectious diseases in the future.